Pengaruh Pengungkapan Key Audit Matters dan Kompetensi Auditor terhadap Kualitas Audit: Studi Empiris pada Kantor Akuntan Publik di Indonesia - Apriliany, Vivi; Pebriyani, Dewi (Universitas Negeri Padang, 2025)
This study aims to determine the effect of key audit matters (KAM) disclosure and auditor competence on audit quality (an empirical study of public accounting firms in Indonesia). The population in this study was all external auditors working at Public Accounting Firms (KAP) in Indonesia registered with the Indonesian Institute of Certified Public Accountants. The sampling technique used simple random sampling. The sample size was determined using the Lemeshow formula. The total sample size in this study was 121 external auditors. This research is quantitative. The data source in this study was primary data distributed by questionnaires to external auditors through the LinkedIn platform. Data analysis used multiple linear regression. The results of this study indicate that key audit matters (KAM) disclosure and auditor competence have a positive and significant effect on audit quality.